Kawaii-style pedagogical agents designs in virtual learning environment: a research conceptual framework - Ahmad Nizam Othman (Tanjong Malim, 2021)
Kawaii-style pedagogical agents designs in virtual learning environment: a research conceptual framework by Ahmad Nizam Othman